Reading Skills of Elementary Pupils as Basis for an Intervention Plan: The Case of Don E. Sero Elementary School, Philippines - Bagolong, Noraima; Usop, Alibai (JPAIR Institutional Research, 2021)
Every pupil who starts primary school learns to read during his/her ordinary developmental period and makes sense of the text. However, even if some pupils learn to read, they have difficulty reading fluently and experiencing problems in understanding what they read. This study aimed to determine the reading skills of Grade II pupils at Don E. Sero Elementary School with an end to propose an intervention, innovation, and strategy. The study is a descriptive survey utilizing a researcher-made questionnaire administered to 56 pupils who are non-readers, using purposive sampling, employing frequency counts, percentage, and mean. Findings revealed that reading skills in terms of phonemic awareness were high, which has helped understand how pupils acquire the ability to read the text in which their future achievement in reading is greatly enhanced. Reading comprehension is revealed to be high as pupils comprehend what they are reading, their effectiveness and pleasure in reading increase. Thus, non-readers must be adequately guided to learn in any school subject and to pass high-stakes tests. However, it is suggested that there is a need to propose an intervention, innovation, and strategy to sustain their reading performance especially understanding profound Filipino texts.